Empirical analysis of the determinants of dairy consumption expenditure in the Accra and Kumasi Peri-Urban communities in Ghana - Aidoo, Robert (2011)
A thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the award of Master of Science